CoMET: a randomised controlled trial of co-commencement of metformin versus placebo as an adjunctive treatment to attenuate weight gain in patients with schizophrenia newly commenced on clozapine. (October 2021) - Siskind, Dan; Russell, Anthony W.; Suetani, Shuichi; Flaws, Dylan; Kisely, Steve; Moudgil, Vikas; Northwood, Korinne; Robinson, Gail; Scott, James G.; Stedman, Terry; Warren, Nicola; Winckel, Karl; et al.
Background: There is limited evidence on interventions to minimise weight gain at clozapine commencement. We compared the effect of adjunctive metformin versus placebo at clozapine initiation. Methods: People with schizophrenia commencing on clozapine were randomised to either metformin or placebo for 24 weeks. The primary outcome was difference in the change of body weight. Secondary outcomes included comparative rates of weight gain of more than 5%, overall weight gain/loss, and differences in metabolic and psychosis outcomes. Results: The study was closed prematurely in March 2020 due to COVID-19 restrictions. Ten participants were randomised to each of the metformin and placebo groups. Eight metformin group and five placebo group participants completed the trial and were included in the analysis. The study was insufficiently powered to detect difference between the metformin and placebo groups for the primary outcome of change in weight (0.09 kg vs 2.88 kg, p  = 0.231). In terms of secondary outcomes, people in the metformin group were significantly less likely to gain >5% of their body weight (12.5% vs 80%, p  = 0.015) and were more likely to lose weight (37.5% vs 0% p  = 0.024) compared to placebo. There was no difference between the groups in terms of adverse drug reactions (ADRs). Conclusion: While limited by the forced premature closure of the trial due to COVID19, the findings from this randomised controlled trial are promising. Clozapine and metformin co-commencement may be a promising treatment to prevent clozapine-associated weight gain, especially given the low rates of ADRs associated with metformin. This supports the consideration of use of metformin to prevent weight gain in people initiated on clozapine; however, further studies are needed to confirm this finding. Trial registration: ACTRN12617001547336